Kemampuan Menghitung Denah dan Skala Menggunakan Problem Based Learning, Auditory Intellectually Repetition, dan Teams Games Tournament di Sekolah Dasar - Davit Tariyo Liono; Darmiyati (Jurnal Pendidikan Sosial Dan Konseling, 2025)
There are still issues related to low activity, critical thinking skills, and student learning outcomes in this study. The aim of the research was to describe teacher activities, analyze student activities, critical thinking skills, and learning outcomes. This study employed Classroom Action Research conducted over four meetings. The research was carried out at SDN Kebun Bunga 6 Banjarmasin, involving 21 fifth-grade students during the 2023/2024 academic year. The data collected included both qualitative and quantitative information. The success indicator for learning completeness was set at 80%, with students achieving a minimum score of ≥65. The results indicated that teacher activity received a “Very Good” rating by the fourth meeting. Class-wide student activity reached 95% with a “Very Active” rating at the fourth meeting. Class-wide critical thinking skills scored 90% with a “Very Skilled” rating at the fourth meeting. Student learning outcomes reached 95% class-wide at the fourth meeting. The implication of this research suggests that the implementation of Problem Based Learning, Auditory Intellectually Repetition, and Teams Games Tournament models can enhance student activity, critical thinking skills, and learning outcomes.